An Analysis of Oil Price Volatility Using VAR: Evidence From Pakistan - Abdul Rafay; Saqib Farid (The Lahore Journal of Business)
Oil is a crucial economic input and Pakistan’s growth, production levels, and price levels are affected significantly by oil price volatility. This paper captures the impact of oil price shocks on Pakistan’s economy by considering variables such as gross domestic product, the wholesale price index, and largescale manufacturing index. Our analysis is based on vector autoregression and the results are in line with similar studies. We also determine the precise shortterm or long-term impact of oil price volatility on the relevant variables.